Teacher team-based incentives: evidence from a natural experiment in a chinese middle school - Leong, Kaiwen (2022)
Using a natural experiment, we examine the causal effect of a team incentive scheme on teachers in a Chinese middle school that intended to help the school's students improve in their weak subjects. The scheme was successful, the average treatment effect is positively significant in math and total scores. The most improvement observed in top students' weak subjects. The top students weak in math, English and social science improved in those subjects by 0.12, 0.10, 0.16 standard deviations, respectively. Students at the bottom 20% of the testing distribution also improved in Chinese and math.